Applications of Digital Image Processing XLIV (SPIE / International Society for Optical Engineering, 2021)
Proceedings of SPIE offer access to the latest innovations in research and technology and are among the most cited references in patent literature. The papers in this volume were part of the technical conference on Applications of Digital Image Processing XLIV held on 1-5 August 2021, San Diego, California, United States.